Religion as makeover: Reality, lifestyle and spiritual transformation. (May 2015) - Deller, Ruth A
In this article I discuss the relationship between religion, spirituality and processes of makeover and transformation as presented in a number of British reality television shows. Programmes including The Monastery, The Convent and Make Me a Muslim placed participants in scenarios where they experimented with adopting religious or spiritual practices as part of their journey of self-transformation. I argue that the nature of transformation in these programmes is in line with standard reality and makeover television practices. However, it also makes a claim to be more 'authentic' than these because of its unfolding within the more traditional environs of religious communities from which makeover culture's narratives of transgression, repentance and salvation were originally derived.